Habitat selection of Dendrocygna javanica in heterogeneous lakes of Malaysia - Martins, Chukwuemeka Onwuka; Rajpar, Muhammad Nawaz; Abu Bakar, Siti Nurhidayu; Hussin, Mohamed Zakaria (SciTechnol, 2017)
Monitoring the habitat selection of lesser whistling Duck (Dendrocygna javanica) is highly crucial for species conservation and management. In this study, habitat selection of D. javanica in 14 heterogeneous lakes (direct visual observation and point sampling technique) and foraging ecology (scan through method) was investigated through April-September, 2016. It was observed that lake Belibis L1 was heavily preferred by D. javanica (i.e., 166.16 individuals) and less preferred lake Kemoning L11 (i.e., 0.2 individuals). However, three lakes i.e., Seroja L2, Telipok L3 and Drift Wood L4 were completely avoided by D. javanica (i.e., no individual was observed) during the study period. The highest pH value was observed in lake Grebe L8 (September 2016; 8.9) and the lowest one in lake Seroja L2 (May 2016; 6.3). Likewise, the highest mean water temperature was recorded in lake Senduduk L6 (June 2016; 32.9 C°) and the lowest one was determined in lake Grebe L8 (July 2016; 20.7 C°). Multivariate analysis i.e., correlation matrix identified multi-collinearity relationship between relative abundance of lesser whistling Duck with Water Level Fluctuation (WLF),Water Quality Index (WQI), Lake Size (LS) and Normalized Difference Vegetation Index (NDVI). Inter-specific variation analysis showed that habitat selection by D. javanica occurs at a species-specific level in responses to changes inenvironmental factors. For example, the highest abundance occurred at minimum water depth (i.e., slope ± SE=-0.004 ± 0.309; P<0.001) while the lowest one at water quality index (slope ± SE=0.069±0.309; P<0.001), lake size (slope ± SE=0.028 ± 13.731; P<0.001), and NDVI (slope ± SE= 6.273 ± 13.731; P<0.001) respectively. This study indicated that habitat type and composition has a great effect on the population of D. javanica. Also it shows that D. javanica preferred shallow lakes rich with aquatic plants and aquatic invertebrates.